ANALISIS KEBIJAKAN DISKRESI AKRUAL TERHADAP SISA LEBIH (KURANG) PERHITUNGAN ANGGARAN - Abdul Rohman (AKUNTABILITAS, 2016)
The aim of this research would like to see the implementation of accrual accounting basis on Local Government and wanted to investigate whether there is influence of discretionary accruals due to the local government revenue. In theory,  accrual basis of accounting is based on the process of recording the transaction on the aspect of the occurrence of an event, although there is no  an element of receipts or cash disbursements. The government has issued regulations governing the Minister of Home Affair  on the implementation of the implementation of the accrual accounting system of local government. Also from the government has issued Government Regulation No. 71 of 2010 concerning the Government Accounting Standard (PSAP) based on accruals. This study uses a model approach Jones. Reports we examined, among others, the budget realization reports, operations statement (LO), balance sheets and statements of cash flows. Our results indicate that local governments have attempted to apply the accrual in accordance with existing regulations. The impact of the implementation of accrual showed abnormal discreation are worth negative. This indicates that there Decrease income.